Effects of tax climate on individual tax compliance quality and minimisation in Malaysia - Chong, K-Rine (2019)
The tax literature has been developing dynamically by combining the economic and socio-psychological factors in explaining tax compliance behaviour. In that tax legality has not been rigorously studied in the past, plus the perception of the authorities that stringent enforcements will enhance voluntary tax compliance, which contradicts the tax literature, this study extends the slippery slope framework. It does this by exploring different dimensions of both compliance quality and tax minimisation behaviour, which comprises legal mitigation, as well as illegal avoidance and evasion under different tax climates, while controlling gender and perceived tax cheating as covariates via MANCOVA. Additionally, this study aims to evaluate the extent of tax minimisation (by percentage) before and after the disclosure of enforcement strategies by climate treatment via the Wilcoxon Signed Rank Test. A multi-method design is employed with 102 undergraduate business students under the experimental design; in addition to 101 postgraduate students, 100 employed, and 100 self-employed groups under the survey design. It is confirmed that enforcement strategies are particularly effective under the synergistic climate. The initial tax minimisation by participants via avoidance or evasion was significantly reduced once they were informed of the probability of being detected and penalised, provided that they perceived a synergistic climate with trust and legitimate power. Overall, a synergistic climate has a significantly large impact on voluntary compliance across the design and subgroups in this study. As opposed to past literature, a synergistic climate increases enforced compliance of the experimental subjects and postgraduate survey subgroup. It seems that university students who lack real experience in fulfilling tax obligations tend to comply under the prevailing positive climate due to fear of penalisation, in addition to their intrinsic willingness as a contribution to society. The selfemployed group in particular, is not very much affected by enforcements, and is not forced to comply in accordance with the tax climate. In general, the majority of citizens are not aware of the legality of tax minimisation, particularly between the grey area of legal mitigation and illegal avoidance. This might explain the issue of validity and low loadings which lead to the insignificant relationship of mitigation with the independent variable and covariates across all groups. For both illegal minimisations of avoidance and evasion, it is proven that they are positively related to the antagonistic climate across groups. In addition, both covariates of gender and morale are related to several variables in different groups. The inferences made in this study provide theoretical and policy implications. Notably, stringent enforcements are only effective in enhancing voluntary compliance and reducing illegal tax minimisation when trust is maintained, and power is perceived as legitimate. Tax authorities and the government should put more effort into building trust and acting fairly upon tax administration and the redistribution of tax collection with due care. From the methodological aspect, it will contribute to conducting a controlled experiment on employed and self-employed samples in future research.